High-performance 3D printing concrete and preparation method thereof

By using precise combination of cement, fly ash, silica fume and other components in 3D printed concrete, we work together to improve the strength, toughness and durability of the material, and solve the bottleneck problems of existing 3D printed concrete in terms of fluidity, interlayer bonding and crack resistance, achieving efficient and stable 3D printing effect.

CN119797838APending Publication Date: 2025-04-11SMARCRETE TECHNOLOGY (HANGZHOU) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411979844.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Existing 3D printed concrete has bottlenecks in terms of fluidity, interlayer bonding and crack resistance, which is difficult to meet construction needs.

Method used

Through precise component design, cement, fly ash, silica fume, fine aggregate, polyvinyl alcohol fiber, nanocellulose, graphene oxide, hydroxyapatite and other components are used to work together to improve the strength, toughness and durability of the material.

Benefits of technology

It significantly improves the strength, toughness, crack resistance, interlayer bonding and durability of 3D printed concrete, optimizes rheology performance and printing adaptability, and is suitable for a variety of complex printing scenarios.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221281240000131
    Figure BDA0005221281240000131
  • Figure BDA0005221281240000141
    Figure BDA0005221281240000141
Patent Text Reader

Abstract

The invention discloses high-performance 3D printing concrete and a preparation method thereof, and relates to the technical field of concrete preparation, and the 3D printing concrete comprises the following components by weight: 30-50 parts of cement; 10 to 20 parts of fly ash; 5 to 10 parts of silica fume; 20 to 40 parts of fine aggregate; 10 to 15 parts of water; 0.05 to 0.2 part of polyvinyl alcohol fiber; 0.01 to 0.1 part of nano cellulose; 0.005 to 0.02 part of graphene oxide; 0.1 to 0.3 part of hydroxyapatite; 0.2 to 0.5 part of a thickening agent; 0.1 to 0.3 part of a dispersant; 0.5 to 1 part of a bonding reinforcing agent; and 0.01 to 0.05 part of a defoaming agent. The printing concrete has the effects of improving the strength, toughness, crack resistance, interlayer binding force and durability of the printing concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of concrete preparation, and in particular to high-performance 3D printing concrete and a preparation method thereof. Background Art

[0002] As an innovative construction technology, 3D printing concrete can achieve rapid prototyping of complex structures by stacking them layer by layer, and has the advantages of high efficiency, material saving and flexible design. However, existing 3D printing concrete faces multiple technical bottlenecks in practical applications and is difficult to fully meet construction needs.

[0003] At present, there are the following problems in the performance design of 3D printing concrete materials: First, there is a contradiction between rheological properties and stability. 3D printing concrete needs to have good fluidity during the printing process to ensure smooth discharge, and at the same time requires the material to harden quickly to maintain the shape stability of the printed layer, but existing materials are difficult to achieve a balance between fluidity and stability, which often leads to problems such as collapse or deformation during the printing process. Second, the interlayer bonding force is insufficient. The layer-by-layer stacking characteristics of 3D printing concrete make the interlayer bonding force a key factor in determining the overall structural strength, but the existing materials have poor bonding performance at the cold joints between layers, which can easily lead to a decrease in mechanical properties and insufficient durability. Third, the crack control effect is limited. Traditional concrete is prone to microcracks during the hardening process, and this problem is more serious for 3D printing concrete due to the particularity of the construction method, affecting the overall stability and service life of the structure.

[0004] Although existing technologies have attempted to optimize the performance of 3D printed concrete by adding fly ash, silica fume, thickeners, dispersants and other components, these improvement schemes are usually difficult to take into account all the performance. Although excessive viscosity can improve shape retention, it will increase pumping resistance; and increasing fluidity may cause the printed layer to lose stability. At the same time, there is a lack of effective solutions for crack control and interlayer bonding in existing technologies, and further optimization is still needed.

[0005] Therefore, developing a new type of concrete material that can simultaneously meet the requirements of 3D printing and solve bottleneck problems in fluidity, interlayer bonding strength and crack resistance has become a technical problem that needs to be urgently solved in this field. Summary of the invention

[0006] In view of the deficiencies in the prior art, the object of the present invention is to provide a high-performance 3D printed concrete and a preparation method thereof.

[0007] The above object of the present invention is achieved through the following technical solutions:

[0008] A high performance 3D printing concrete comprising the following components in weight percentage:

[0009] Cement: 30-50 parts;

[0010] Fly ash: 10-20 parts;

[0011] Silica fume: 5-10 parts;

[0012] Fine aggregate: 20-40 parts;

[0013] Water: 10-15 parts;

[0014] Polyvinyl alcohol fiber: 0.05-0.2 parts;

[0015] Nanocellulose: 0.01-0.1 parts;

[0016] Graphene oxide: 0.005-0.02 parts;

[0017] Hydroxyapatite: 0.1-0.3 parts;

[0018] Thickener: 0.2-0.5 parts;

[0019] Dispersant: 0.1-0.3 parts;

[0020] Adhesion enhancer: 0.5-1 part;

[0021] Defoaming agent: 0.01-0.05 parts.

[0022] The 3D printing concrete of the present invention has shown significant advantages in strength, toughness and durability through precise formula design. With cement as the main cementitious material, combined with fly ash and silica fume, the volcanic ash reaction and filling effect are fully utilized to improve the density and impermeability of concrete, while effectively reducing the hydration heat, meeting the needs of complex construction conditions of 3D printing.

[0023] The synergistic effect of polyvinyl alcohol fibers and nanocellulose plays a key role in enhancing the toughness and crack resistance of the material. The three-dimensional distribution of polyvinyl alcohol fibers provides crack bridging function, preventing crack propagation through stress transfer; nanocellulose forms a microscopic network structure in the slurry, and its excellent suspension stability and adhesion improve the bonding effect between the fiber and the matrix, further enhancing the interlayer bonding force and the stability of the printing process. In addition, nanocellulose improves the overall performance by limiting the movement of fibers in the slurry and ensuring uniform fiber distribution.

[0024] The introduction of graphene oxide further improves the comprehensive performance of concrete. Its flaky structure and high specific surface area improve the interfacial wettability and dispersibility, while enhancing the thermal conductivity and fracture toughness, effectively reducing the risk of cracks induced by thermal stress during 3D printing. The synergistic effect of graphene oxide and nanocellulose improves the interface uniformity and mechanical properties of the slurry, while significantly improving the crack resistance and thermal conductivity. The flaky structure of graphene oxide disperses the stress concentration area and delays the formation of microcracks, while the hydrogen bonding between it and nanocellulose enhances the interfacial adhesion between the matrix and the reinforcing components.

[0025] The addition of hydroxyapatite gives the material excellent corrosion resistance and biocompatibility, making it have broad potential in specific application scenarios such as medical and building repair. Hydroxyapatite effectively inhibits crack propagation by filling the micropores in the concrete matrix and combines with the crack bridging effect of polyvinyl alcohol fibers, and provides a chemical barrier in corrosive environments, greatly improving corrosion resistance. The synergistic effect of hydroxyapatite and graphene oxide further improves the microstructural stability and crack resistance of concrete, while giving the material a certain electrochemical self-healing ability, significantly improving compressive strength and durability.

[0026] In addition, the combination of graphene oxide and polyvinyl alcohol fiber effectively reduces the risk of cracks caused by thermal stress during printing by controlling cracks and improving thermal conductivity. The intermolecular forces between the polar groups of graphene oxide and the fibers further enhance the interlayer bonding strength. The use of thickeners and dispersants optimizes the rheological properties of the slurry to ensure a smooth and accurate printing process; the bonding enhancer improves the interlayer bonding strength; and the defoamer reduces the bubble content and improves the density and compressive strength of the material.

[0027] In summary, through precise component design and synergistic enhancement, the 3D printed concrete material of the present invention shows excellent performance in mechanical properties, crack resistance, interlayer bonding strength and durability.

[0028] Furthermore, the average diameter of the polyvinyl alcohol fiber is 10-20 μm and the length is 3-6 mm.

[0029] The precise control of the diameter and length range of polyvinyl alcohol fibers ensures that the fibers do not significantly reduce the fluidity of the slurry while enhancing the toughness and crack resistance of concrete, thus adapting to the needs of 3D printing equipment. Fibers with a diameter of 10-20μm can provide moderate tensile strength and are tightly bonded to the concrete matrix. Fibers with a length of 3-6mm ensure uniform fiber distribution and will not cause local material performance degradation or blockage of the printing nozzle. The optimized geometric size design further enhances the bridging ability of microcracks and significantly improves the crack resistance and fatigue resistance of concrete.

[0030] Furthermore, the nanocellulose is cellulose nanocrystals or cellulose nanofibers, with an average length of 100-200 nm and a diameter of 10-30 nm.

[0031] By selecting cellulose nanocrystals or cellulose nanofibers as reinforcing components, the toughness and interfacial bonding properties of the material are effectively improved. The high regularity of cellulose nanocrystals and the high aspect ratio of cellulose nanofibers provide excellent mechanical reinforcement effects. At the same time, by optimizing the size range of 100-200nm in length and 10-30nm in diameter, it is ensured that it is evenly distributed in the matrix without agglomeration. This design overcomes the defects of traditional reinforcing materials that are easy to settle or unevenly distributed, further improves the homogeneity of concrete and the interlayer bonding strength, and is particularly suitable for the layered manufacturing characteristics of 3D printing.

[0032] Furthermore, the graphene oxide is a flake structure with a flake thickness of less than 2 nm and a lateral size of 0.5-5 μm.

[0033] The graphene oxide flaky structure maximizes its dispersibility and interfacial force in the concrete matrix by optimizing its flaky layer thickness of less than 2nm and lateral size of 0.5-5μm. The physical and chemical reinforcement effect formed by the flaky structure in the matrix can significantly improve the crack resistance, wear resistance and thermal conductivity of concrete. In addition, the high specific surface area of ​​graphene oxide can form a synergistic effect with other components (such as nanocellulose and hydroxyapatite) to further enhance the comprehensive performance of concrete. Compared with traditional graphene, the size design of graphene oxide in the present invention is more suitable for 3D printing applications, which effectively solves the problems of insufficient interlayer bonding and printing cracks.

[0034] Furthermore, the thickener is hydroxypropyl methylcellulose or polyvinyl alcohol.

[0035] The thickener is hydroxypropyl methylcellulose or polyvinyl alcohol, which has a good rheological property adjustment effect, can significantly improve the printability of concrete slurry, and ensure the stability of the material and interlayer adhesion during the printing process. The thickener is matched with the dispersant and defoamer to form a good balance of fluidity, anti-segregation and interfacial bonding, which provides a guarantee for the high-precision implementation of the 3D printing process.

[0036] Furthermore, the dispersant is a polycarboxylic acid water reducer.

[0037] The dispersant is a polycarboxylic acid water-reducing agent, which significantly reduces water consumption and improves the compressive strength and density of concrete by improving the dispersibility of the slurry. At the same time, the synergistic effect with nanocellulose and graphene oxide optimizes the internal microstructure of the material and enhances the uniformity and quality stability of printing.

[0038] A method for preparing high-performance 3D printed concrete comprises the following steps:

[0039] Step 1: Weigh the raw materials according to the proportion of each component;

[0040] Step 2: Mix fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite in a dry state to obtain a mixed powder;

[0041] Step 3: Add water, thickener, dispersant, bonding enhancer and defoamer to the mixed powder in sequence, stir evenly to form a homogeneous concrete slurry;

[0042] Step 4: Let it sit for 5-10 minutes and remove the bubbles before using it for 3D printing.

[0043] The preparation method of 3D printed concrete scientifically optimizes the material preparation process through multiple steps to ensure uniform distribution of each component and good interface bonding performance, especially the dry mixing design of fine aggregate, cement and functional nano components, which significantly improves the homogeneity of the mixture, thereby improving the stability of the overall performance of the material. The sequential addition of functional components in step 3 helps to achieve the gradual dispersion and combination of the components, so that the slurry can avoid stratification, sedimentation or unevenness while maintaining fluidity. The synergistic effect of the static process and the defoamer in step 4 effectively removes bubbles in the slurry, ensuring the high density and mechanical properties of the material.

[0044] Furthermore, the dry mixing time in step 2 is 3-5 minutes, and the stirring speed is 300-500 rpm.

[0045] By optimizing the dry mixing time and mixing speed, the matrix materials such as fine aggregate and cement are fully and evenly mixed with the functional components to avoid material agglomeration or stratification, thereby improving the uniformity and printing performance of concrete.

[0046] Furthermore, the stirring time in step 3 is 5-8 minutes, and the nanocellulose and graphene oxide are gradually added during the stirring process.

[0047] The stirring time and the gradual addition of functional nanocomponents further ensured the fluidity and stability of the slurry.

[0048] Furthermore, after the stirring in step 3 is completed, a defoaming agent is added, and a vacuum degassing device is used to reduce bubbles before standing.

[0049] The introduction of a vacuum degassing device in combination with a defoaming agent not only effectively removes tiny bubbles, but also improves the density of the slurry and the interlayer bonding strength of the printed structure.

[0050] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:

[0051] The 3D printing concrete of the present invention significantly improves the strength, toughness, crack resistance, interlayer bonding and durability of the material through formula design and corresponding preparation process, while optimizing rheological properties and printing adaptability. By utilizing the synergistic effect of functional components such as nanocellulose, graphene oxide, hydroxyapatite, and the application of industrial by-products such as fly ash and silica fume, excellent mechanical properties, corrosion resistance and environmental benefits are achieved. Its preparation process is efficient and simple, the material has good uniformity, and it is suitable for a variety of complex printing scenarios. It has broad application prospects in the fields of construction, restoration and special engineering. DETAILED DESCRIPTION

[0052] The present invention is described in detail below in conjunction with embodiments.

[0053] Example 1

[0054] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0055] Cement: 30 parts (P.O42.5R rapid hardening ordinary Portland cement);

[0056] Fly ash: 10 parts;

[0057] Silica fume: 5 parts;

[0058] Fine aggregate: 20 parts;

[0059] Water: 10 parts;

[0060] Polyvinyl alcohol fiber: 0.05 parts (average diameter 15 μm, length 4 mm);

[0061] Nanocellulose: 0.01 parts (cellulose nanocrystals, average length 150 nm, diameter 20 nm);

[0062] Graphene oxide: 0.005 parts (sheet structure, sheet thickness 1.5nm, lateral size 2μm);

[0063] Hydroxyapatite: 0.1 parts;

[0064] Thickener: 0.2 parts (hydroxypropyl methylcellulose, viscosity 2000mPa·s);

[0065] Dispersant: 0.1 part (polycarboxylic acid water reducer, the main component is polyvinyl ether side chain structure);

[0066] Adhesion enhancer: 0.5 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0067] Defoaming agent: 0.01 part (polyether-siloxane composite type).

[0068] Preparation method:

[0069] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0070] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 3 minutes, and the stirring speed is 400 rpm.

[0071] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 5 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0072] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 5 minutes to eliminate bubbles.

[0073] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0074] Example 2

[0075] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0076] Cement: 50 parts (P.O52.5R rapid hardening ordinary Portland cement);

[0077] Fly ash: 20 parts;

[0078] Silica fume: 10 parts;

[0079] Fine aggregate: 40 parts;

[0080] Water: 15 parts;

[0081] Polyvinyl alcohol fiber: 0.2 parts (average diameter 20 μm, length 6 mm);

[0082] Nanocellulose: 0.1 parts (cellulose nanofibers, average length 200 nm, diameter 30 nm);

[0083] Graphene oxide: 0.02 parts (sheet structure, sheet thickness 1nm, lateral size 5μm);

[0084] Hydroxyapatite: 0.3 parts;

[0085] Thickener: 0.5 parts (hydroxypropyl methylcellulose, viscosity 4000mPa·s);

[0086] Dispersant: 0.3 parts (polycarboxylate water reducer, high fluidity formula);

[0087] Adhesion enhancer: 1 part (redispersible latex powder, modified ethylene-vinyl acetate copolymer);

[0088] Defoaming agent: 0.05 parts (silicone).

[0089] Preparation method:

[0090] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0091] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 5 minutes, and the stirring speed is 500 rpm.

[0092] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 2 minutes to form a homogeneous concrete slurry.

[0093] S4. Defoaming and standing: After adding the defoamer, stir for another minute and then let the concrete slurry stand for 10 minutes to eliminate bubbles.

[0094] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0095] Example 3

[0096] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0097] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0098] Fly ash: 15 parts;

[0099] Silica fume: 7 parts;

[0100] Fine aggregate: 30 parts;

[0101] Water: 12 parts;

[0102] Polyvinyl alcohol fiber: 0.1 part (average diameter 18 μm, length 5 mm);

[0103] Nanocellulose: 0.05 parts (cellulose nanocrystals, average length 180 nm, diameter 25 nm);

[0104] Graphene oxide: 0.01 parts (sheet structure, sheet thickness 1.2nm, lateral size 3μm);

[0105] Hydroxyapatite: 0.2 parts;

[0106] Thickener: 0.3 parts (hydroxypropyl methylcellulose, viscosity 3000mPa·s);

[0107] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0108] Adhesion enhancer: 0.8 parts (redispersible latex powder);

[0109] Defoaming agent: 0.02 parts (polyether).

[0110] Preparation method:

[0111] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0112] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 4 minutes, and the stirring speed is 450 rpm.

[0113] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 2 minutes to form a homogeneous concrete slurry.

[0114] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 7 minutes to eliminate bubbles.

[0115] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0116] Example 4

[0117] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0118] Cement: 35 parts (P.O42.5 ordinary Portland cement);

[0119] Fly ash: 12 parts;

[0120] Silica fume: 6 parts;

[0121] Fine aggregate: 25 parts;

[0122] Water: 12 parts;

[0123] Polyvinyl alcohol fiber: 0.08 parts (average diameter 12 μm, length 3 mm);

[0124] Nanocellulose: 0.02 parts (cellulose nanocrystals, average length 120 nm, diameter 15 nm);

[0125] Graphene oxide: 0.007 parts (sheet structure, sheet thickness 1.8nm, lateral size 3μm);

[0126] Hydroxyapatite: 0.15 parts;

[0127] Thickener: 0.25 parts (hydroxypropyl methylcellulose, viscosity 1500mPa·s);

[0128] Dispersant: 0.15 parts (polycarboxylic acid water reducer, the main component is polyvinyl ether side chain structure);

[0129] Adhesion enhancer: 0.7 parts (redispersible latex powder);

[0130] Defoaming agent: 0.015 parts (polyether).

[0131] Preparation method:

[0132] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0133] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 4 minutes, and the stirring speed is 400 rpm.

[0134] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0135] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 7 minutes to eliminate bubbles.

[0136] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0137] Example 5

[0138] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0139] Cement: 50 parts (P.O52.5R rapid hardening ordinary Portland cement);

[0140] Fly ash: 10 parts;

[0141] Silica fume: 8 parts;

[0142] Fine aggregate: 30 parts;

[0143] Water: 14 parts;

[0144] Polyvinyl alcohol fiber: 0.15 parts (average diameter 16 μm, length 4 mm);

[0145] Nanocellulose: 0.03 parts (cellulose nanofibers, average length 180 nm, diameter 25 nm);

[0146] Graphene oxide: 0.01 parts (sheet structure, sheet thickness 1.3nm, lateral size 4μm);

[0147] Hydroxyapatite: 0.2 parts;

[0148] Thickener: 0.4 parts (hydroxypropyl methylcellulose, viscosity 3000mPa·s);

[0149] Dispersant: 0.25 parts (polycarboxylate water reducer);

[0150] Adhesion enhancer: 0.9 parts (redispersible latex powder, modified ethylene-vinyl acetate copolymer);

[0151] Defoaming agent: 0.03 parts (polyether-siloxane composite type).

[0152] Preparation method:

[0153] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0154] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state for 5 minutes at a stirring speed of 450 rpm.

[0155] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 5 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0156] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 8 minutes to eliminate bubbles.

[0157] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0158] Example 6

[0159] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0160] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0161] Fly ash: 15 parts;

[0162] Silica fume: 7 parts;

[0163] Fine aggregate: 35 parts;

[0164] Water: 13 parts;

[0165] Polyvinyl alcohol fiber: 0.1 part (average diameter 18 μm, length 5 mm);

[0166] Nanocellulose: 0.04 parts (cellulose nanocrystals, average length 150 nm, diameter 20 nm);

[0167] Graphene oxide: 0.008 parts (sheet structure, sheet thickness 1.6nm, lateral size 3μm);

[0168] Hydroxyapatite: 0.18 parts;

[0169] Thickener: 0.35 parts (hydroxypropyl methylcellulose, viscosity 2500mPa·s);

[0170] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0171] Adhesion enhancer: 0.8 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0172] Defoaming agent: 0.02 parts (polyether).

[0173] Preparation method:

[0174] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0175] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 4 minutes, and the stirring speed is 400 rpm.

[0176] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0177] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 9 minutes to eliminate bubbles.

[0178] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0179] Comparative Example 1

[0180] This comparative example discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0181] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0182] Fly ash: 15 parts;

[0183] Silica fume: 7 parts;

[0184] Fine aggregate: 35 parts;

[0185] Water: 13 parts;

[0186] Thickener: 0.35 parts (hydroxypropyl methylcellulose, viscosity 2500mPa·s);

[0187] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0188] Adhesion enhancer: 0.8 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0189] Defoaming agent: 0.02 parts (polyether).

[0190] Preparation method:

[0191] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0192] S2. Dry mixing: Mix fine aggregate, cement, fly ash and silica fume evenly in a dry state, with a dry mixing time of 4 minutes and a stirring speed of 400 rpm.

[0193] S3. Slurry preparation: Add water, thickener, dispersant and adhesion enhancer to the mixed powder in sequence and stir for 6 minutes to form a homogeneous concrete slurry.

[0194] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 9 minutes to eliminate bubbles.

[0195] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0196] Comparative Example 2

[0197] This comparative example discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0198] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0199] Fly ash: 15 parts;

[0200] Silica fume: 7 parts;

[0201] Fine aggregate: 35 parts;

[0202] Water: 13 parts;

[0203] Polyvinyl alcohol fiber: 0.1 part (average diameter 18 μm, length 5 mm);

[0204] Nanocellulose: 0.04 parts (cellulose nanocrystals, average length 150 nm, diameter 20 nm);

[0205] Graphene oxide: 0.008 parts (sheet structure, sheet thickness 1.6nm, lateral size 3μm);

[0206] Thickener: 0.35 parts (hydroxypropyl methylcellulose, viscosity 2500mPa·s);

[0207] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0208] Adhesion enhancer: 0.8 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0209] Defoaming agent: 0.02 parts (polyether).

[0210] Preparation method:

[0211] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0212] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume and polyvinyl alcohol fiber are mixed evenly in a dry state, the dry mixing time is 4 minutes, and the stirring speed is 400 rpm.

[0213] S3. Slurry preparation: Add water, thickener, dispersant, and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose and graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0214] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 9 minutes to eliminate bubbles.

[0215] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0216] Comparative Example 3

[0217] This comparative example discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0218] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0219] Fly ash: 15 parts;

[0220] Silica fume: 7 parts;

[0221] Fine aggregate: 35 parts;

[0222] Water: 13 parts;

[0223] Graphene oxide: 0.008 parts (sheet structure, sheet thickness 1.6nm, lateral size 3μm);

[0224] Hydroxyapatite: 0.18 parts;

[0225] Thickener: 0.35 parts (hydroxypropyl methylcellulose, viscosity 2500mPa·s);

[0226] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0227] Adhesion enhancer: 0.8 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0228] Defoaming agent: 0.02 parts (polyether).

[0229] Preparation method:

[0230] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0231] S2. Dry mixing: Mix fine aggregate, cement, fly ash, silica fume and hydroxyapatite evenly in a dry state, with a dry mixing time of 4 minutes and a stirring speed of 400 rpm.

[0232] S3. Slurry preparation: add water, thickener, dispersant, and adhesion enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add graphene oxide, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0233] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 9 minutes to eliminate bubbles.

[0234] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0235] Comparative Example 4

[0236] This embodiment discloses a high-performance 3D printing concrete, the specific components and proportions of which are as follows (by weight):

[0237] Cement: 40 parts (P.O42.5 ordinary Portland cement);

[0238] Fly ash: 15 parts;

[0239] Silica fume: 7 parts;

[0240] Fine aggregate: 35 parts;

[0241] Water: 13 parts;

[0242] Polyvinyl alcohol fiber: 0.1 part (average diameter 18 μm, length 5 mm);

[0243] Nanocellulose: 0.04 parts (cellulose nanocrystals, average length 150 nm, diameter 20 nm);

[0244] Hydroxyapatite: 0.18 parts;

[0245] Thickener: 0.35 parts (hydroxypropyl methylcellulose, viscosity 2500mPa·s);

[0246] Dispersant: 0.2 parts (polycarboxylate water reducer);

[0247] Adhesion enhancer: 0.8 parts (redispersible latex powder, ethylene-vinyl acetate copolymer);

[0248] Defoaming agent: 0.02 parts (polyether).

[0249] Preparation method:

[0250] S1. Weighing of raw materials: Accurately weigh each component according to the above ratio.

[0251] S2. Dry mixing: fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite are mixed evenly in a dry state, the dry mixing time is 4 minutes, and the stirring speed is 400 rpm.

[0252] S3. Slurry preparation: Add water, thickener, dispersant and bonding enhancer to the mixed powder in sequence, stir for 6 minutes, then gradually add nanocellulose, and continue stirring for 3 minutes to form a homogeneous concrete slurry.

[0253] S4. Defoaming and standing: After adding the defoaming agent, stir for another minute and then let the concrete slurry stand for 9 minutes to eliminate bubbles.

[0254] S5. Printing preparation: After the static state is completed, the concrete slurry is loaded into the 3D printing equipment for printing.

[0255] Detection Methods

[0256] The 3D concrete printed by Examples 1-6 and Comparative Examples 1-3 was subjected to the following tests:

[0257] 1. Corrosion resistance test

[0258] Take a standard cubic test block of each concrete formula, with a size of 100mm×100mm×100mm, and cure it for 28 days. Then soak the test blocks in the following corrosive solutions for a test period of 30 days:

[0259] 1) 5% sulfuric acid solution (acidic environment);

[0260] 2) 3% sodium chloride solution (salt spray environment);

[0261] 3) Saturated sodium sulfate solution (sulfate corrosion environment).

[0262] Detection indicators:

[0263] 1) The mass change rate of the test block before and after the test;

[0264] 2) The compressive strength retention rate of the test block after the test;

[0265] 3) Surface cracks and color changes.

[0266] The test results are shown in Table 1:

[0267] Table 1

[0268] Sample No. Mass loss rate (%) Compressive strength retention rate (%) Surface changes Example 1 0.8 96 No obvious cracks or discoloration on the surface Example 2 0.6 98 Smooth surface and complete structure Example 3 0.7 97 Slight discoloration, no obvious cracks Example 4 0.9 95 Minor cracks, localized slight erosion Example 5 0.5 99 Smooth surface, completely crack-free Example 6 0.7 96 The surface is uniform and has no obvious damage Comparative Example 1 2.5 85 Severe surface cracks and significant quality degradation Comparative Example 2 1.8 88 Surface cracks expand and local pieces fall off Comparative Example 3 2 87 Corners are falling off and the surface is obviously rough

[0269] 2. Crack resistance test

[0270] A concrete slab with a size of 400 mm × 100 mm × 50 mm was printed and cured for 14 days. A three-point bending test machine was used to apply a load to the concrete slab until cracks appeared. The first crack load (the value at which the load first causes cracks), crack extension length, and crack width were tested. The test results are shown in Table 2.

[0271] Table 2

[0272] Sample No. First crack load(kN) Crack width(mm) Crack extension length (mm) Example 1 15 0.2 25 Example 2 18 0.15 20 Example 3 16 0.18 22 Example 4 14 0.22 30 Example 5 19 0.12 18 Example 6 17 0.16 21 Comparative Example 1 8 0.35 50 Comparative Example 2 10 0.3 45 Comparative Example 3 9 0.32 48

[0273] 3. Compression test

[0274] Take a standard cubic test block (100mm×100mm×100mm) and cure it for 28 days. Use a hydraulic universal testing machine to gradually load until the test block is crushed. Record the compressive strength (MPa) of the sample, as shown in Table 3.

[0275] Table 3

[0276]

[0277]

[0278] 4. Durability test

[0279] A standard cubic test block (100 mm × 100 mm × 100 mm) was subjected to 100 freeze-thaw cycles between -20°C and +20°C. After the freeze-thaw cycles, the mass loss rate and compressive strength retention rate of the test block were measured.

[0280] Using an impermeability tester, after the standard cubic test block is subjected to a water pressure of 3 MPa for 12 hours, the water penetration depth of the standard cubic test block is recorded.

[0281] The test results are shown in Table 4.

[0282] Table 4

[0283] Sample No. Freeze-thaw cycle loss rate (%) Compressive strength retention rate (%) Penetration depth (mm) Example 1 0.5 95 2 Example 2 0.3 97 1.5 Example 3 0.4 96 1.8 Example 4 0.6 94 2.2 Example 5 0.2 98 1.3 Example 6 0.4 96 1.7 Comparative Example 1 2 85 4 Comparative Example 2 1.8 86 3.8 Comparative Example 3 1.9 84 3.9

[0284] It can be seen from the above tests that the comprehensive performance of the embodiment is far better than that of the comparative example, which is manifested in four aspects: corrosion resistance, crack resistance, compression resistance and durability. The synergistic effect of nanocellulose, graphene oxide and hydroxyapatite used in the embodiment significantly improves the corrosion resistance of the material. Polyvinyl alcohol fiber and nanocellulose inhibit the generation and expansion of cracks, providing a significant toughening effect. Graphene oxide and thickener work together to significantly improve the strength and density of concrete, and the maximum compressive strength reaches 60MPa. The freeze-thaw loss rate of the embodiment is low, and the compressive strength retention rate is high, indicating that it has excellent durability. This is mainly due to the reinforcing effect of graphene oxide and hydroxyapatite, which significantly improves the frost resistance and impermeability of concrete.

[0285] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.

Claims

1. A high-performance 3D printed concrete, characterized in that: The composition includes the following weight percentages: Cement: 30-50 parts; Fly ash: 10-20 parts; Silica fume: 5-10 parts; Fine aggregate: 20-40 parts; Water: 10-15 parts; Polyvinyl alcohol fiber: 0.05-0.2 parts; Nanocellulose: 0.01-0.1 parts; Graphene oxide: 0.005-0.02 parts; Hydroxyapatite: 0.1-0.3 parts; Thickener: 0.2-0.5 parts; Dispersant: 0.1-0.3 parts; Adhesion enhancer: 0.5-1 part; Defoaming agent: 0.01-0.05 parts.

2. The 3D printed concrete according to claim 1, characterized in that: The average diameter of the polyvinyl alcohol fiber is 10-20 μm, and the length is 3-6 mm.

3. The 3D printed concrete according to claim 1, characterized in that: The nanocellulose is cellulose nanocrystals or cellulose nanofibers, and has an average length of 100-200 nm and a diameter of 10-30 nm.

4. The 3D printed concrete according to claim 1, characterized in that: The graphene oxide is a flake structure, the flake thickness is less than 2nm, and the lateral size is 0.5-5μm.

5. The 3D printed concrete according to claim 1, characterized in that: The thickener is hydroxypropyl methylcellulose or polyvinyl alcohol.

6. The 3D printed concrete according to claim 1, characterized in that: The dispersant is a polycarboxylate water reducer.

7. A method for preparing 3D printed concrete according to claims 1-6, characterized in that: The following steps are involved: Step 1: Weigh the raw materials according to the proportion of each component; Step 2: Mix fine aggregate, cement, fly ash, silica fume, polyvinyl alcohol fiber and hydroxyapatite in a dry state to obtain a mixed powder; Step 3: Add water, thickener, dispersant, bonding enhancer and defoamer to the mixed powder in sequence, stir evenly to form a homogeneous concrete slurry; Step 4: Let it sit for 5-10 minutes and remove the bubbles before using it for 3D printing.

8. The preparation method according to claim 7, characterized in that: The dry mixing time in step 2 is 3-5 minutes, and the stirring speed is 300-500 rpm.

9. The preparation method according to claim 7, characterized in that: The stirring time in step 3 is 5-8 minutes, and nanocellulose and graphene oxide are gradually added during the stirring process.

10. The preparation method according to claim 7, characterized in that: After the stirring is completed in step 3, add the defoamer and use a vacuum degassing device to reduce bubbles before standing.